Exploring the Contribution of Fintech to Digital Transformation in Indonesian MSMEs: A Literature Review - Febriyani, Widia; Supratman, Nurdinintya Athari; Witjaksono, R.Wahjoe (Sistemasi: Jurnal Sistem Informasi, 2024)
In the digital era, Financial Technology (Fintech) has become a pivotal force in transforming business operations, particularly for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Despite their significant contributions to the economy, MSMEs need help in adopting digital solutions, including limited access to financial services and technological integration. This study explores the role of Fintech in driving the digital transformation of MSMEs and examines its contributions to financial inclusion, operational efficiency, and market expansion. Through a systematic literature review, the study highlights key factors influencing Fintech adoption, such as digital literacy, regulatory support, and technological infrastructure. The research also discusses the potential of Fintech to support the Satu Data Indonesia initiative by integrating financial and operational data. However, barriers such as low digital literacy, complex regulations, and cybersecurity concerns persist. The findings provide valuable insights for policymakers and practitioners to develop effective strategies for supporting MSMEs in leveraging Fintech for sustainable growth and competitiveness.